ENGLISH LEARNING NEEDS OF TECHNOLOGY INFORMATICS COMPUTER STUDENTS: AN ESP ANALYSIS - Sevrika, Hevriani; Mayuasti, Mayuasti; Zurniati, Vivi; Junialdi, Rezi (TELL - US JOURNAL, 2025)
AbstractTechnology Information students need the material in English subject that relate with their department. However, most of the lecturers used the materials in general English in working fields. Thus, in this research the writer did it to know the students’ need. In this research, the samples are the students in the technology informatics computer department. There is one class which is 28 students. The writer took all students through technology informatics computer sampling is total sampling. The instrument that writer used to take the data is questionnaires through close – ended questions. The design of this research is descriptive quantitative research. Then, the findings reveal that, in terms of necessities, students require English materials that are simple, relevant to IT contexts, and easy to understand. Regarding lacks, students have limited vocabulary, which hinders their ability to comprehend reading texts. Concerning wants, students express a strong desire to improve their speaking fluency; however, classroom instruction rarely provides sufficient opportunities for speaking practice. The results suggest that English teachers should design and implement learning materials that are contextually relevant to the IT and emphasize communicative activities to enhance students’ speaking competence.